2018
DOI: 10.1186/s40862-018-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of L2 vocabulary instruction: a meta-analysis

Abstract: The purpose of the present meta-analysis is to the investigate the overall effectiveness of L2 vocabulary instruction and to find the moderator variables affecting its effectiveness. By defining a rigorous inclusion and exclusion criteria, a total number of 16 primary studies (N = 1008), 7 published and 9 Ph.D. dissertations, were included. Under Random-Effects Model, the overall effect size of (d = 0.80) was observed. After conducting Q test of heterogeneity, a number of moderator variables were examined; con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…To date, some topics related to vocabulary in EFL/L2 have been investigated. In particular, the vocabulary knowledge of EFL learners has attracted increasing attention (Rassaei, 2017;Yousefi and Biria, 2018). Some studies have examined EFL learners' vocabulary learning through explicit instruction (Mizumoto and Takeuchi, 2009), computer-assisted language learning (Shokrpour et al, 2019;Namaziandost et al, 2021), extensive reading (Liu and Zhang, 2018;Song, 2020), and repeated reading (Liu and Todd, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…To date, some topics related to vocabulary in EFL/L2 have been investigated. In particular, the vocabulary knowledge of EFL learners has attracted increasing attention (Rassaei, 2017;Yousefi and Biria, 2018). Some studies have examined EFL learners' vocabulary learning through explicit instruction (Mizumoto and Takeuchi, 2009), computer-assisted language learning (Shokrpour et al, 2019;Namaziandost et al, 2021), extensive reading (Liu and Zhang, 2018;Song, 2020), and repeated reading (Liu and Todd, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Through vocabulary learning, L2 learners can achieve mastery over the second language (Nation, 2008). Since practitioners and scholars have come to realize the integral role of vocabulary learning in communication and language learning, more research attention has been given to L2 vocabulary instruction (Rassaei, 2017;Yousefi and Biria, 2018;Liu et al, 2020). L2 literature has observed a growing interest in exploring effective explicit and implicit strategies such as using dictionaries, inferring word meaning from context, and extensive reading for learning collocations and vocabulary in particular (see Hunt and Beglar, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Factors found to influence the difficulties of ELLs in learning have been explored in several studies ( Dussling, 2018 ; Thompson and von Gillern, 2020 ; Yousefi and Bria, 2018 ). There are two main reasons for these difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, I explore classroom work with literature which involves two teachers and their students within adult second language education. Previous research has shown the potential for language development in reading literature (Krashen, 1985(Krashen, , 2013Mason, 2013;Yousefi & Biria, 2018), how literature can play a part in transforming the perspective of adult learners (Mezirow, 1996;Janks, 2010;Jarvis, 2012;King, 2000; see also Hoggan, 2016;Taylor & Cranton, 2013) and in in reclaiming radical perspectives on learning and citizenship (Gouthro & Holloway, 2013). There are also studies on the reading of literature in contexts where adults study language and literature out of interest (Carroli, 2011;Saal & Dowell, 2014).…”
Section: Introductionmentioning
confidence: 99%